Multilevel Analysis of Socioeconomic Determinants on Diabetes Prevalence, Awareness, Treatment and Self-Management in Ethnic Minorities of Yunnan Province, China - Su, Rong (Int J Environ Res Public Health, 2016)
Objectives: The objective of this manuscript is to investigate socioeconomic differences in prevalence, awareness, treatment and self-management of diabetes among ethnic minority groups in Yunnan Province, China. Methods: We conducted a cross-sectional survey in a sample of 5532 Na Xi, Li Su, Dai and Jing Po ethnic minorities. Multilevel modeling was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for diabetes prevalence, as well as the other outcomes. Results: Higher individual educational level was associated with a higher rate of awareness, treatment, adherence to medicines and monitoring of blood glucose (OR = 1.87, 4.89, 4.83, 6.45; 95% CI: 1.26–2.77, 1.87–12.7, 1.95–11.9, 2.23–18.6, respectively). Diabetic respondents with better household assets tended to receive more treatment (OR = 2.81, 95% CI: 1.11–7.12) and to monitor their blood glucose (OR = 3.29, 95% CI: 1.48–7.30). Diabetic patients with better access to medical services were more likely to treat (OR = 7.09, 95% CI: 2.46–20.4) and adhere to medication (OR = 4.14, 95% CI: 1.46–11.7). Income at the contextual level was significantly correlated with diabetes prevalence, treatment and blood glucose monitoring (OR = 1.84, 3.04, 4.34; 95% CI: 1.20–2.83, 1.20–7.73, 1.45–13.0, respectively). Conclusions: Future diabetes prevention and intervention programs should take both individual and township-level socioeconomic factors into account in the study regions.